Tax Reform and Economic Growth: A Meta-Analysis - Jayanti, Al Frida (Advances in Taxation Research, 2024)
Purpose: This study aims to comprehensively examine the relationship between tax reform and economic growth through synthesizing existing empirical research. Research Design and Methodology: The research design involved a systematic review and meta-analysis of studies examining the impact of tax policy on economic performance. Findings and Discussion: Findings from the literature synthesis point to the multifaceted nature of this relationship, revealing a positive association between tax cuts and economic growth and dynamics influenced by institutional quality, policy design, and country-specific characteristics. Implications: Policymakers, researchers, and stakeholders can use these insights to develop informed strategies for harnessing tax reform's potential to promote sustainable and inclusive economic growth.